Confinement efficacy of partially and fully wrapped CFRP systems in RC column prototypes - Ferreira, Débora R. S. M. (2006)
Since the beginning of the nineties, fibre reinforced polymers (FRP) have been used to increase the load carrying capacity and the energy absorption capacity of reinforced concrete columns [1-5]. The high specific strength and stiffness, the low thickness and weight, and the high resistance to corrosion of FRP materials are favourable properties justifying the increase use of these composites in the structural upgrading [6]. The full wrapping FRP-technique is the most used to increase the load carrying capacity and the energy absorption capacity of reinforced concrete (RC) columns. However, preliminary tests with concrete elements submitted to direct compressive loading revealed that partial wrapping (strips of CFRP sheets) is a promising confinement technique [7]. Since in concrete columns deserving strengthening intervention there are always a certain percentage of steel hoops, the application of CFRP strips in-between the existent steel hoops can be an adjusted confinement technique with technical and economical advantages, when full wrapping is taken for basis of comparison. To assess the efficacy of the partial wrapping technique, 108 prototypes of RC columns were confined by distinct CFRP arrangements and tested under direct compression. The experimental program was designed to evaluate the influence of the following variables on the compression behavior: stiffness of the wet lay-up CFRP sheet; distance between CFRP strips; width of the CFRP strip; number of CFRP layers per each strip; concrete strength; percentage of the steel longitudinal and tranversal reinforcement ratios. The present work describes the experimental program and presents and analyzes the obtained results. Using the obtained experimental results, the applicability of a confinement model [8] was appraised for the RC columns partially wrapped.